Zagadnienie dopuszczalności zbiegu ról procesowych członka komisji habilitacyjnej i członka organu habilitującego - Bogusz, Mariusz (PRAWO i WIĘŹ, 2025)
In habilitation proceedings, an issue arises concerning the admissibility of the concurrence of procedural roles held by, on the one hand, a member of the habilitation committee (the body entrusted with evaluating the scholarly achievements of a candidate and providing an opinion on the application for the conferment of the habilitation degree, i.e. the Polish post-doctoral degree) and, on the other hand, a member of the habilitation authority (the body empowered to make the decision on the conferment of the habilitation degree). The way this problem is resolved is of fundamental importance for the correctness of the proceedings and the decision concerning the conferment of the habilitation degree. The author examines this issue in the light of the Act – Law on Higher Education and Science, as well as within the framework of the Code of Administrative Procedure. The analysis leads to the conclusion that, with respect to five members of the habilitation committee, such a concurrence of procedural roles is categorically precluded, whereas in the case of two members of the habilitation committee – by reason of their distinct legal status – such a concurrence is both possible and legally permissible.